2017
DOI: 10.1111/psyp.13039
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotionally valenced eye region images on visuocortical processing of surprised faces

Abstract: In this study, we presented pictorial representations of happy, neutral, and fearful expressions projected in the eye regions to determine whether the eye region alone is sufficient to produce a context effect. Participants were asked to judge the valence of surprised faces that had been preceded by a picture of an eye region. Behavioral results showed that affective ratings of surprised faces were context dependent. Prime-related ERPs with presentation of happy eyes elicited a larger P1 than those for neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…no hair), though this was necessary to avoid changing the size of the core facial features, which are known to strongly impact ERP amplitudes (e.g. eyes, see Li et al , 2018). Moreover, tiredness or habituation effects might be involved, as participants completed two other face experiments directly preceding the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…no hair), though this was necessary to avoid changing the size of the core facial features, which are known to strongly impact ERP amplitudes (e.g. eyes, see Li et al , 2018). Moreover, tiredness or habituation effects might be involved, as participants completed two other face experiments directly preceding the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, for fearful faces, the eyes constitutea crucial region for recognising the emotional expression (e.g. see Adolphs, 2008; Wegrzyn et al , 2015), as well as for modulating ERP responses (Li et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the effect of emotional faces on ERPs, several components are of interest: The P1 component peaks between 80 and 120 ms after stimulus presentation, is influenced by endogenous and exogenous spatial attention and related to early processes of stimulus detection (Clark & Hillyard, 1996; Eimer, van Velzen, & Driver, 2002; Herrmann & Knight, 2001; Hillyard & Anllo‐Vento, 1998). Regarding the contribution of fearful expressions, mixed findings on P1 modulations are reported: While some studies observed larger P1 amplitudes for fearful faces (e.g., see Li, Li, Wang, Zhu, & Luo, 2018; Santos, Iglesias, Olivares, & Young, 2008; Smith, Weinberg, Moran, & Hajcak, 2013), others did not find such an effect (e.g., see Acunzo, MacKenzie, & van Rossum, 2019; Mavratzakis, Herbert, & Walla, 2016; Wieser, Gerdes, Greiner, Reicherts, & Pauli, 2012). Recent studies suggest that low‐level features contribute strongly to P1 effects (Schindler, Bruchmann, Gathmann, Moeck, & Straube, 2019), indicating that physical differences account at least partly for the diversity of these results.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one study found that participants made more cooperative decisions after supraliminal eye contact than they did with no eye contact, and the effect only existed for the prosocial but not for the pro-self [23]. To date, research using eye stimuli alone to study face processing is still in an initial stage [24]. Additionally, emotions conveyed by eye region information become more important and a necessary way for people to read others’ mind when expressions of the others’ whole face is not available, such as in medical situations or hijacking.…”
Section: Introductionmentioning
confidence: 99%